2016
DOI: 10.3758/s13414-016-1230-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of implicit and explicit temporal expectation on choice response time and response conflict

Abstract: People can use temporally structured sensory information to anticipate future events. Temporal information can be implicitly presented through probability manipulation without participants’ awareness of the manipulation, or explicitly conveyed through instructions. We examined how implicit and explicit temporal information established temporal expectations that influenced choice response times and response conflicts (measured as flanker effects). We implicitly manipulated temporal structure by block-wise varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 46 publications
2
18
1
1
Order By: Relevance
“…Another factor that may impact the effect of temporal expectation on memory is awareness of the imposed timing manipulation. That awareness may be important, is suggested by studies in the perception literature that indicate that the benefits of expectation on perception are larger when instructions include specific information about the timing manipulation (Menceloglu et al, 2017 ). In three experiments reported here, just one participant (from Experiment 1) reported having noticed a difference between encoding blocks on the PEQ.…”
Section: Discussionmentioning
confidence: 98%
“…Another factor that may impact the effect of temporal expectation on memory is awareness of the imposed timing manipulation. That awareness may be important, is suggested by studies in the perception literature that indicate that the benefits of expectation on perception are larger when instructions include specific information about the timing manipulation (Menceloglu et al, 2017 ). In three experiments reported here, just one participant (from Experiment 1) reported having noticed a difference between encoding blocks on the PEQ.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, accuracy and RT effects only emerged in Experiment 2, in which accuracy was higher and RT was faster in the predictable than the unpredictable conditions. Some studies have reported effects of temporal expectation on accuracy and RT 12 , 13 , 14 , 15 but others have failed to find such effects 3 , 16 , 17 . Some task demands and/or stimulus parameters may be responsible for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…First, TEs might be generated automatically by encapsulated bottom-up mechanismsin these cases, explicit knowledge might not affect the strength of TE (Ball et al, 2018a(Ball et al, , 2018bShen & Alain, 2012;Visser, Tang, Badcock, & Enns, 2014). Second, knowledge about likely time points of target occurrence might enhance perception and preparation for events at these time points, thereby increasing the size of the TE effect (Coull & Nobre, 1998;Menceloglu, Grabowecky, & Suzuki, 2017). Finally, participants might apply their knowledge in a truly optimal fashion and attend every relevant temporal position successively (for a discussion of optimal temporal strategies, see Ball, Michels, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%